Stress Causing Factors Among Teachers in Elementary Schools and Their Relationship with Demographic and Job Characteristics - Agai-Demjaha, Teuta; Jordan Minov; Sasho Stoleski; Beti Zafirova (ID Design 2012/DOOEL Skopje, 2015)
Once high levels of work-related stress among teachers were confirmed many studies concentrated on identifying and investigating key stress factors among school teachers. Unfortunately there are very few researches made on stress causing factors among teachers in Republic of Macedonia.
Keywords: workplace; stress causing factors; teachers; elementary school; job characteristics